Spatial Variation of In Vitro Starch and Protein Digestibility in White Wheat Bread. (23rd March 2018) - Alvarez‐Ramirez, Jose; Rodriguez‐Huezo, Eva; Meraz, Monica; Garcia‐Diaz, Samuel; Flores‐Silva, Pamela C.; Mondragon‐Reinoso, Lorena
Abstract : The digestibility of bread components is an important issue for the design of healthy food products. The in vitro starch and protein digestibility, and the associated morphology, moisture content, thermal (differential scanning calorimetry), and structural (Fourier transform infrared spectroscopy) changes are determined on samples obtained from different radial locations of white wheat bread slices immediately after baking. Experimental results indicated that starch in the crumb region was more digestible (≈86% RDS), while the crust region contained higher amount of slowly digestible starch (≈22%). On the other hand, the crust region had lower protein content than the crumb region, but the latter showed higher digestibility (≈96%). The results shows that digestibility of starch and proteins in wheat bread is not uniform, but exhibits important variations from crumb to crust likely induced by spatial moisture and temperature profiles during baking. Abstract : The effect of the spatial radial location on the morphology and physicochemical properties of bread slices is evaluated. The protein digestibility and RS content decreases with the relative position to the slice center. Meanwhile the SDS demonstrates the opposite behavior. DSC and FTIR are performed to monitor the associated changes in the thermal and structural properties of bread.